2016
DOI: 10.1111/joa.12469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different fixation protocols on the preservation and dimensions of cardiac tissue

Abstract: Recent extensive progress in invasive cardiac procedures has triggered a wave of dozens of heart morphometric anatomical studies that are carried out largely using autopsied samples fixed in formaldehyde solution prior to observations and measurements. In reality, very little is known about changes in heart tissue dimensions during fixation. The aim of this study was therefore to investigate how fixation affects the dimensions of cardiac tissue, and if different types and concentrations of reagents affect this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 13 publications
1
40
1
Order By: Relevance
“…First, the main limitation of this study was the use of formaldehyde‐fixed postmortem specimens, which might give a bias in the measurements. However, previous studies have shown that the measurements after fixation in 10% paraformaldehyde, especially those associated with the vessel diameters and angle dimensions, are similar to those before fixation and can be considered nonsignificant . Nevertheless, reported in this study dimensions of the coronary veins’ ostia may be considered to be lower when compared to everyday clinical practice.…”
Section: Discussioncontrasting
confidence: 44%
“…First, the main limitation of this study was the use of formaldehyde‐fixed postmortem specimens, which might give a bias in the measurements. However, previous studies have shown that the measurements after fixation in 10% paraformaldehyde, especially those associated with the vessel diameters and angle dimensions, are similar to those before fixation and can be considered nonsignificant . Nevertheless, reported in this study dimensions of the coronary veins’ ostia may be considered to be lower when compared to everyday clinical practice.…”
Section: Discussioncontrasting
confidence: 44%
“…Although high quality immunestaining results are acquired, our data suggest that NBF is not a proper fixative for histological analysis of blastema tissue. Alcoholic formalin is especially appropriate for fixation of polysaccharides (Hoda et al, 2016). According to our results, integrity of blastema tissues is maintained by its usage in histological analysis.…”
Section: Discussionmentioning
confidence: 85%
“…The main limitation is that all measurements and observations were made on autopsied heart specimens after paraformaldehyde fixation, which could affect tissue size. However, previous studies have shown that 10% paraformaldehyde does not cause atrial tissue dimensions to differ significantly from those before fixation (Hołda et al, ). Another limitation is that we are unable to draw conclusions about the behavior and dimension changes of the studied area within the cardiac cycle.…”
Section: Discussionmentioning
confidence: 89%